Assessment of aflatoxin in milk and feed samples and impact of seasonal variations in the Punjab, Pakistan. Issue 6 (14th April 2020) - Akbar, Naveed; Nasir, Muhammad; Naeem, Naureen; Ahmad, Mansur‐ud‐Din; Saeed, Farhan; Anjum, Faqir Muhammad; Iqbal, Sanaullah; Imran, Muhammad; Tufail, Tabussam; Shah, Faiz‐ul‐Hassan; Atif, Muhammad
Abstract: The present study was designed to assess the incidence of aflatoxin contamination in animal feed and raw milk samples (total 240 each) collected from dairy farms during the complete year of 2015. These samples were collected through a cluster random sampling technique by dividing the province of Punjab, Pakistan into five clusters (north, south, east, west and central). Factors (environmental & physical) affecting aflatoxin contamination in milk and animal feed at farms were also studied. The AFM1 levels in raw milk & AFB1 levels in feed samples were analyzed by using the ELISA technique. Results demonstrated that overall about 53% raw milk samples from dairy farms were contaminated beyond the US MRL (0.50 µg/L) for AFM1 with than average level of 0.59 µg/L, while the 95% farm feed samples were exceeding the FDA MRL (20 µg/kg) of AFB1 with average level of 43 µg/kg. During winter season, the concentration of AFM1 was higher in all clusters with avg 0.68 µg/L, while the AFB1 contamination was highest in the spring season with avg 54 µg/kg. Market feed prices had negative correlation with AFB1 contamilevels, which were further supported by the positive correlation between quantity of feed at farms with AFM1 and AFB1 contamination. Results exhibited significantly positive impact of environmental factors on milk and feed aflatoxin contamination levels, whereas temperature showed an inverse relationship with AFM1 and AFB1 levels. The study recommends need of synergistic extension work to support dairy farms and highlight the contamination levels for regulatory bodies to introduce strategic policies for control measures. Abstract : Study recommends dire need of synergistic extension work for the awareness and motivation of farmers. Moreover, this extensive screening facility highlights government authorities to establish mechanism of support required to the farmers in postharvest handling, drying, storage, and transportation of agriculture produce. Strategic actions and policies must implement to make aflatoxin‐free milk supply chain.